Identification of types and abundance of microplastics in coastal sediments of Tanjung Jumlai Beach, North Penajam Paser Regency, East Kalimantan - Mayasari , Siti; Ghitarina , Ghitarina; Mustakim, Mohammad (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
The existence of microplastics is affected by the many activities in the community related to the use of plastic, as well as uncontrolled disposal of plastic waste so that plastic waste enters the waters through water flows and will degrade into smaller sizes. This research aims to identify the type, abundance, and composition, as well as determine differences in abundance between types of microplastics in Tanjung Jumlai Beach sediments. Sampling was conducted by drawing a transect line 100 meters long, then dividing it into 5 lanes each measuring 20 meters. Each lane was subdivided into sub-transect boxes measuring 5×5 meters. Then, within each 5×5 meter sub-transect, 1×1 meter sub-transect boxes were created, making 25 sub-transect boxes of 1×1 meter in each 20-meter lane. From these, 5 boxes were selected using randomizer application. Sediment samples that have been processed were then identified using a microscope. There were three types of microplastics found in Tanjung Jumlai beach, namely 65% fragments with an abundance of 10.340 particles/kg/m2, 19% fiber with an abundance of 2.960 particles/kg/m2, and 16% film with an abundance of 2.580 particles/kg/m2. There is a significant difference in abundance between fragment microplastics and film and fiber microplastics. There is no significant difference in abundance between film microplastics and fiber microplastics found on the coast of Tanjung Jumlai, Penajam Paser Utara Regency, East Kalimantan.